Pengaruh Likuiditas dan Profitabilitas, terhadap Nilai Perusahaan Manufaktur Sub Sektor Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Agustina Waromi; Maria Wesso; Fenska Mbaubedari (Jurnal Manajemen Bisnis Era Digital, 2025)
This study is titled The Effect of Liquidity and Profitability on the Firm Value of Chemical Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange in the 2019–2021 Period. The study aims to assess the development and the partial and simultaneous effects of liquidity and profitability on firm value. This quantitative research used data from 12 manufacturing companies in the chemical subsector listed on the IDX. Data collection was conducted through documentation and literature study, and the analysis was carried out using descriptive and inferential statistics with the SmartPLS 3.8 application. The results show that partially, liquidity has a negative but insignificant effect on firm value, with a significance value of 0.331. Conversely, profitability has a positive and significant effect on firm value with significance values of 0.037 and 0.000. Simultaneously, liquidity and profitability have a positive and significant effect on firm value, indicated by a t-value of 13.671 and a significance level of 0.000. The coefficient of determination (R²) of 59.2% indicates that liquidity and profitability explain the firm value, while the remaining 40.8% is explained by other variables. The study suggests that chemical subsector companies need to improve their financial performance to enhance their firm value.